SPE Annual Technical Conference and Exhibition 2016
DOI: 10.2118/181315-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach to Measure the RealTime Data Quality Using Key Performance Indicators

Abstract: After the setup of a real-time drilling data feed from the Rig site to the operations center, the obvious question is - How good is the data that is being streamed? Real-Time rig sensor data could be an effective input for drilling optimization, However, the confidence in the results of these analysis or interpretations is directly associated to the trustworthiness of the data acquired. Measuring the quality of the data has been a difficult issue for many years. This paper shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These KPIs are utilized within a Real-Time Data Quality Dashboard, allowing drilling engineers to filter analysis results based on acceptable data quality ranges. This systematic methodology facilitates the identification of high-performing rigs and those in need of improvement [8] Javed et.al highlighted the critical role of flat-time operations in oil and gas well construction, specifically focusing on the Blowout Preventer (BOP) handling to control costs and enhance safety. Through a case study of 14 wells in Malaysia, it was found that BOP-related activities significantly contribute to overall flat time.…”
Section: Introductionmentioning
confidence: 99%
“…These KPIs are utilized within a Real-Time Data Quality Dashboard, allowing drilling engineers to filter analysis results based on acceptable data quality ranges. This systematic methodology facilitates the identification of high-performing rigs and those in need of improvement [8] Javed et.al highlighted the critical role of flat-time operations in oil and gas well construction, specifically focusing on the Blowout Preventer (BOP) handling to control costs and enhance safety. Through a case study of 14 wells in Malaysia, it was found that BOP-related activities significantly contribute to overall flat time.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The rig site practices propose to add/develop more sensors 7 , 11 and to standardize the transmission and text abbreviation. 12 The administrative approaches propose using key performance indicators (KPIs) to evaluate the quality of data 12 and to develop a data quality dashboard, 13 real-time data quality center, 12 , 14 and others. The method approaches apply a manual cleansing process, 7 remove bias, 15 remove outliers, 16 correlate the data together, 17 smooth the data set, 7 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the literature defining metrics for completeness, further research is performed using and evaluating the introduced metrics for sensor and actuator data. For example, Otalvora et al, 2016 [41] use task-independent record completeness to assess the data quality of sensor data from drilling rigs. However, on record level, the task-dependent attribute is limited to concerns regarding the amount of data.…”
mentioning
confidence: 99%